Barbershop Reservation System (e-Barber) / Mohamad Akmal Arif Mazlan - Mazlan, Mohamad Akmal Arif (2018)
Nowadays, number of barbershops are increasing day and these barbershops company must provide many uniqueness to compete with other competitors to attract customers to come to their barbershops. Currently, they are only using ‘walk-in’ (manual system) to customers get their services. The main problem is longer waiting time for customer to take turn and customer cannot choose their preferred barber. By implementing an online barbershop reservation system (e-Barber), it can ease customer and bring benefits to the management. The agile model which is extreme programming methodology is used in the development of the system. The methodology consists of five phases which are requirement planning phase, analysis phase, design phase, development phase, testing phase and lastly the documentation. This system has been evaluated by 30 respondent and 4 expert in multiple field that related in the development system. The evaluation has been made by distributed the questionnaires to all the respondents. In a nutshell, it will help the barbershop to retain their customer loyalty towards their barbershop.